Version [2.0] — [pyMCMA: Uniformly distributed Pareto-front representation] - Marek Makowski; Janusz Granat; Andrii Shekhovtsov; Zbigniew Nahorski; Jinyang Zhao (SoftwareX)
pyMCMA is the Python implementation of a novel method for autonomous computation of the Pareto-front representation composed of efficient solutions distributed uniformly in terms of the distances between neighbor Pareto solutions. pyMCMA supports scientific, i.e., objective, model analysis by providing preference-free Pareto front representation.The update provides new functionalities and enhancements. The former include clustering of the Pareto-front solutions. The enhancements include internal software improvements, optional customization of some parameters, as well as a new functionalities that might be used by advanced users.